Teachers’ Use of Wait Time: A Case Study of Questioning Strategies in SMAN Padang - Fairatul Husna Daslin; Yetti Zainil (Journal of English Language Teaching, 2020)
Not many research done yet on the wait time in classroom especially in the EFL classroom. This study aimed to observe how much time is given by the teacher between question posed and learners’ answers (wait time 1); and wait time 2, between students' feedback and teacher's explanation. This study also investigates the limitation of wait time which was observed using the conversation analysis and Stimulated Recall Interview (SRI). The participants of this study were 12 English teachers in SMAN Padang. The finding showed that most of the teacher waited 1-2 seconds in wait time 1 and wait time 2. The researcher found that the teacher in SMAN Padang gave the recommended wait time 1 (3-5 seconds) with only 25 % of the total questions, and in wait time 2 was  9 %. Moreover, the researcher found that questions types affect the wait time 1. In contrast, it did not occur in wait time 2. The researcher also discovered the phenomenon caused the limitation of wait time 1 and wait time 2. They were teacher echoing, teacher interruption, teacher elaboration, lower order questions and self-answer.